Mengurangi Durasi Penyelesaian Proyek dengan Menggunakan Metode Crashing pada Pembangunan Gedung Kecamatan Lamongan - Dwi Kartikasari; S. W. Sampurno; P. E. Agustyawan (Faculty of Engineering, Kadiri University, 2021)
Cost, quality and time are important aspects planned in the implementation of construction. Achieving optimum quality at a lower cost is the main goal desired in project implementation. This study aims to determine the comparison of project costs with the application of the Crashing method on the Lamongan District building construction project. The normal cost required to carry out the construction is Rp. 1,144,445,838.00 with a project duration of 150 working days. The crashing method is applied by adding additional working hours (overtime). The duration of working hours is increased to 3 hours, so it is expected that with this addition, the volume of work produced is greater. The results of the study obtained that the total cost after being accelerated with the addition of work duration was Rp. 1,162,252,577.00 or more expensive 1.55% of the normal cost and the duration of the project implementation is 143 working days. With this addition, the project duration is faster by 7 days.